2019
DOI: 10.1177/0193945918823347
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an HIV Self-Management Intervention on Neurocognitive Behavioral Processing

Abstract: People living with HIV (PLHIV) are increasingly diagnosed with comorbidities which require increasing self-management. We examined the effect of a self-management intervention on neurocognitive behavioral processing. Twenty-nine PLHIV completed a two-group, 3-month randomized clinical trial testing a self-management intervention to improve physical activity and dietary intake. At baseline and 3 months later, everyone completed validated assessments of physical, diet, and neurocognitive processing (functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, we did not collect data on the number or type of coexisting chronic conditions or perceptions of social support for selfmanagement. Although our results should be interpreted with caution, the current study adds to an emerging body of research exploring associations between brain activation and self-management behaviors related to hypertension self-management and health status (Jones et al, 2019;Webel et al, 2019). Further research is needed to elucidate the underlying mechanisms of brain-based approaches to self-management across populations with different chronic conditions.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 83%
See 4 more Smart Citations
“…For example, we did not collect data on the number or type of coexisting chronic conditions or perceptions of social support for selfmanagement. Although our results should be interpreted with caution, the current study adds to an emerging body of research exploring associations between brain activation and self-management behaviors related to hypertension self-management and health status (Jones et al, 2019;Webel et al, 2019). Further research is needed to elucidate the underlying mechanisms of brain-based approaches to self-management across populations with different chronic conditions.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 83%
“…A few investigations explored the brain–behavior connections of effective self-management of chronic conditions (Jack et al, 2013; Jones et al, 2019; Webel et al, 2019). Using the same fMRI protocol as the study reported herein, in a small study, Webel et al (2019) explored the effects of an HIV self-management intervention (targeting diet and exercise) on neurocognitive, behavioral processing over time, and improvements were observed with TPN task differentiation; however, advances in the neural networks did not demonstrate progress in self-management behaviors (e.g., diet and physical activity). Also, using the protocol used in the current study, Wright et al (2020) found that reported discrimination stress was associated with reduced activation of the DMN and vmPFC in African Americans enrolled in a BP self-management program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations